(untitled) (BIRDEM Medical Journal, 2024)
Background: After cholecystectomy, patients often present with post-cholecystectomy syndrome. Among a handful of causes, remnant gallbladder pathology is a rare entity. We are here presenting a series of remnant gallbladder pathology cases, who were managed laparoscopically. Methods: A prospective study of post-cholecystectomy syndrome patients who showed remnant gall bladder stones in ultrasonogram. Data on diagnostic workup, management and the challenges encountered in handling such patients were collected. Results: Eight patients presented with remnant gall bladder stones, between January 2011 to June 2019. Six of them were female. These patients presented a variable time period after initial surgery, earliest after 3 months, with persistent pain in right hypochondriac region. Difficult cholecystectomy was documented in operation notes of two cases. Seven of them were managed by laparoscopic completion cholecystectomy. Conclusion: A symptomatic gallbladder remnant after cholecystectomy is rarely seen. However, the diagnosis should be considered in patients with recurrent biliary symptoms after a difficult cholecystectomy. Completion cholecystectomy is challenging both for patient as well as the surgeon but it is the definitive treatment for such cases. Laparoscopic completion cholecystectomy is our recommended technique. BIRDEM Med J 2024; 14(1): 43-48